Academic writing : - Bailey, Stephen (Sage Publications Ltd, 2011)
The book is divided into short sections which contain examples, explanations and exercises for use in the classroom or self-study. Cross-references allow easy access to relevant sections, and a full answer key is included. The 3rd edition has been developed in response to suggestions from both students and teachers. Featuring a new website, there is increased coverage of plagiarism, argument, cause and effect, comparison, definitions and academic style. Different forms of writing, including reports and literature reviews, are also covered.